A comparative legal study: legal views on xenotransplantation in the United Kingdom, United States and Malaysia / Syarifah Mohd Nordin, Nur Nabilah Abdul Aziz, Khairil Rizal Rohim - Mohd Nordin, Syarifah; Abdul Aziz, Nur Nabilah; Rohim, Khairil Rizal (2009)
This project paper is focus on the legal perspective of xenotransplantation in the United Kingdom (UK), United States (US) and Malaysia. As there is an ineffectiveness of the xenotransplantation in the UK and US, there is a need to consider that whether the xenotransplantation in Malaysia should be applicable or not. Xenotransplantation defined as the use of animal organs or tissue for human transplantation. The current developments in xenotransplantation raises significant medical concerns since this new technology cause a lot of problems. The issues reviewed include public health risks and safety which xenotransplantation cause the infectious of disease to the world at large. Another issue discussed is the environment, human rights, animal welfare, religious perspective, scientific issues and economic aspects that affect from the research of xenotransplantation. It is submitted that the new law is needed to overcome the problem of xenotransplantation. The application of xenotransplantation in Malaysia should be prohibited considering the external harm is the manifestation of various diseases which defects the human and animal rights, and caused the environmental pollution. Then, in the case of permanent uncertainty about the future life after xenotransplantation, Islam strongly directs one to keep away from destruction; especially pig is the most suitable sources for xenotransplantation